2005
DOI: 10.1530/rep.1.00567
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and leptin as conditional prognostic IVF markers

Abstract: We studied the concentration of serum estradiol and serum and follicular fluid leptin in 200 women undergoing their first in vitro fertilization with embryo transfer (IVF-ET) program at the time of human chorionic gonadotrophin administration and oocyte retrieval, in an attempt to assess their concerted role on embryo quality and the prognosis of IVF outcome. Low serum (46.49 6 8.4 ng/ml) and follicular fluid (52 6 9.8 ng/ml) leptin levels were associated with a high number of 'good-quality' embryos (73.6%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 14 publications
3
35
0
1
Order By: Relevance
“…This lack of correlation suggested that estradiol and leptin might have opposing roles during ovarian stimulation. Their parallel, although disproportional, elevation on the day of hCG administration, however, has been shown to have a negative influence on IVF-ET outcome, in agreement with our recent report (Anifandis et al 2005).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This lack of correlation suggested that estradiol and leptin might have opposing roles during ovarian stimulation. Their parallel, although disproportional, elevation on the day of hCG administration, however, has been shown to have a negative influence on IVF-ET outcome, in agreement with our recent report (Anifandis et al 2005).…”
Section: Discussionsupporting
confidence: 92%
“…3), a finding common to all samples from ART success (positive b-hCG test, pregnant) and failure women (negative b-hCG test, non-pregnant) ( Table 1). The observed variation in leptin but not BMI of women categorized either according to estradiol levels on hCG administration day (Anifandis et al 2005) or ART success/failure women (BMI of ART success women, 21.16^0.88 kg/m 2 and BMI of ART failure women, 23.14^0.85 kg/m 2 , P ¼ not significant) suggests that the relative sensitivities of these two parameters differ with leptin being a far more sensitive IVF marker compared with BMI. In agreement with the leptin levels and in contrast to BMI, embryo quality differed significantly between the two groups being of far superior quality in ART success women (58% vs 32%, P , 0.01) ( Table 1).…”
Section: Clinical Correlations Between Leptin Estradiol and Bmimentioning
confidence: 89%
See 1 more Smart Citation
“…Some prior studies have found a negative correlation with leptin levels and IVF outcomes [10][11][12][13]. The primary difference with our study compared to previous studies was the number of data points for collected leptin samples.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies have shown no correlation of follicular fluid or serum leptin with IVF outcome or sex-steroid levels [8,9]. This is in contrast to other studies which found that low serum and follicular fluid levels of leptin negatively correlated with embryo quality, implantation rates, and pregnancy rates [10][11][12][13]. Follicular fluid concentrations of leptin, estradiol, and progesterone have been evaluated by few studies [10][11][12][13].…”
Section: Introductionmentioning
confidence: 95%